1993
DOI: 10.1080/00071669308417658
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a soluble polysaccharide (carboxy methyl cellulose) on the absorption of minerals from the gastrointestinal tract of broilers

Abstract: 1. The effect of an indigestible soluble polysaccharide (carboxy methyl cellulose: CMC) on the absorption of some macro-elements (sodium, potassium, calcium, phosphorus and magnesium) from different segments of the small intestine of broilers was determined. 2. In semi-synthetic diets 0, 5.0 and 10 g/kg cellulose was replaced by CMC on weight basis. These diets were fed to male broilers from 3 to 5 weeks of age. 3. CMC inclusion reduced the rate of mineral absorption throughout the small intestine. The effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…The increased NSP elevated the viscosity of digesta [16]. Because the high viscosity of intestinal content lowered mineral absorption [17], the present decreased shell ratio might be induced by decreased calcium absorption.…”
Section: Discussionmentioning
confidence: 83%
“…The increased NSP elevated the viscosity of digesta [16]. Because the high viscosity of intestinal content lowered mineral absorption [17], the present decreased shell ratio might be induced by decreased calcium absorption.…”
Section: Discussionmentioning
confidence: 83%
“…Food and water remained available to these birds until killing at 22 d of age, after which they were weighed individually. After killing through injection of 2 ml/bird of T61 (Embutramide-Mebezoniumiodide-Tetracainhydrochloride mix; Hoechst, Munchen, Germany), samples were taken of the jejunum 100 mm preceding Meckel's diverticulum and of the ileum 100 mm preceding the ileo-caecal junction, for determination of jejunal and ileal digestibilities of energy and starch as described by Van der Klis et al (1993). For analysis of the jejunal and ileal contents all fifteen samples per cage were pooled to give four replicate samples per treatment.…”
Section: Additional Measurementsmentioning
confidence: 99%
“…The apparent retention or RBV in tibia of minerals in wheat bran and rice bran ranged from Ca 9.50 to 11.06, P14.56 to 11.26, Mn 0.26 to 0.86, Fe 2.32 to 7.7 and Zn 1.57 to 2.18% receptivity. These differences may be depended to mechanisms physico-chemical properties of dietary cell wall consist of non-starch polysaccharide and lignin in mineral binding are the cation exchange capacity, and compound absorptive properties [3,53]. While insoluble fiber fraction [54].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, published research reported that minerals bioavailability of cereals less or poorly utilized than from animal sources by monogastric animals. Endogenous and exogenous factors have been implicated in reduction of minerals absorption from lignin act as ligands in cereals [11,53,59] and depend on the nature of the lignin [13].…”
Section: Resultsmentioning
confidence: 99%